Surface modification of AISI 316L stainless steel by applying single and multilayer coatings: Study of elastic modulus and antibacterial properties - Bahare Soltani; Sayed Mahmood Rabiee; Salman Nourouzi; Seyed Jamal Hosseinipour; Simindokht Khademjafari (Heliyon)
AISI 316L stainless steel is extensively used in various fields, including medicine. In this study, in order to improve antibacterial properties, reduce elastic modulus, increase hydrophilicity and delay corrosion on the surface of AISI 316L stainless steel pieces for biomedical applications, zinc and magnesium elements were used for coating. Zn monolayer, Zn-Mg bilayer, and Zn-Mg-Zn triple coatings were deposited on AISI 316L substrates using the thermal evaporation method. Field emission scanning electron microscopy (FE-SEM) confirmed the formation of thin film coatings on the substrate. EDX analysis also indicated the presence of Zn and Mg elements in the coatings. Atomic force microscopy (AFM) results showed a reduction in the root mean square roughness in the coated specimens compared to the uncoated ones. This technique was also used to compare the force between the samples. The result of this research indicated 22.78 % increase in hydrophilicity, 31.25 % improvement in antibacterial properties and 86.67 % reduction in elastic modulus when comparing the uncoated sample with the three-layer coated sample. X-ray diffraction (XRD) revealed the intermetallic composition of Zn and Mg. The average crystallite size, determined using Scherer's equation, was 14.61, 13.15, 13.92, and 49.60 nm for the uncoated, one-layer, two-layer, and three-layer samples, respectively. Atomic absorption spectroscopy (AAS) revealed that the 24-h release of Zn2+, Mg2+, and Ni2+ ions from the samples was within the allowable range when immersed in simulated body fluid (SBF). Corrosion measurements indicated the formation of a galvanic cell due to the layers in the coated samples, and the substrate did not corrode until the coating was fully degraded.